2019
DOI: 10.1049/mnl.2018.5447
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic performance of rod‐shaped copper oxides prepared by spin coating

Abstract: Copper oxides (CuO and Cu 2 O), having narrow bandgap and a variety of chemophysical properties, are attractive in many fields such as solar cells, energy conversion, optoelectronic devices, and catalyst. In this work, these copper oxides are synthesised via co-precipitation method and spin coating and annealed in various temperatures. Then, samples are characterised by X-ray powder diffraction, scanning electron microscopy (SEM) and ultraviolet-visible light absorption spectra. From the SEM images of sample a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…of Fe 2 O 3 . According to the pattern and by using Debye–Scherrer equation ( d = ( kλ / β cos θ ) [21], the crystallite size of anatase phase was determined to be of the order of 23 nm.…”
Section: Resultsmentioning
confidence: 99%
“…of Fe 2 O 3 . According to the pattern and by using Debye–Scherrer equation ( d = ( kλ / β cos θ ) [21], the crystallite size of anatase phase was determined to be of the order of 23 nm.…”
Section: Resultsmentioning
confidence: 99%
“…Absorption onset wavelength) λ g , nm) of the crossing point is between the line extrapolated from the onset of the rising part of the absorption spectrum and axis X of the curve. Bandgap ( E g , eV) was measured by the following equation [15]: Eg=1243.1λg …”
Section: Methodsmentioning
confidence: 99%
“…Throughout the examination, a sample of each solution was taken at 30 min intervals, and the concentration of the pollutant was determined utilising a UV–vis spectrophotometer device. The extent of the degradation was measured by the following equation: η%=)(C0CC0×100 where C 0 is the initial concentration of the pollutant in the solution, and C is that of the pollutant after the time t [15].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, Dutta et al [66] and surface area of catalyst need to be taken into consideration to explain the experimentally observed degradation efficiency. For example, in a study reported by Koohestani [68], the degree of elimination of methyl orange using pure CuO NPs was found to be higher than Cu2O/CuO mixture. According to the author, this could be due to the smaller bandgap and larger specific surface area of CuO NPs than the Cu2O/CuO photocatalyst.…”
Section: Effect Of Morphological Properties Of Cuo and Cuo-based Cata...mentioning
confidence: 95%